Compliance na corte interamericana de direitos humanos: um estudo a partir da propriedade comunal indígena - NEVES, Rafaela Teixeira Sena (Universidade Federal do Pará, 2017)
The objective of this study is to examine compliance with the judgments of the Inter- American Court of Human Rights cases involving violation of the territorial rights of Indigenous Peoples, with awards made between of 2001 to 2005. The study of cases Mayagna (Sumo) Awas Tingni vs. Nicaragua and Yakye Axa vs. Paraguay examines the jurisprudential construction of communal property, the Institute of compliance with the inter-American human rights system and the supervision stage of compliance with the judgments made by the Inter-American Court of Human Rights. Seeks to determine whether and how the mechanisms of this system interfere in cases compliance level. The empirical test as a methodology, relates a quantitative and qualitative analysis of compliance with the judgments repair orders. The findings allow us to consider the development of the monitoring mechanism of the system and re-evaluate their effectiveness in the affirmation of Human Rights of Indigenous People.